(untitled) (Academia Journal of Medicine, 2023)
Aphthous ulcers, also known as canker sores, are a common and painful condition affecting the oral mucosa. This review article aims to provide an in depth understanding of aphthous ulcers, including their causes, symptoms, and management. The article examines the different types of aphthous ulcers, their epidemiology, etiology, clinical presentation, and current treatment options.